Quality of Life Among People Living with HIV AIDS in Banda Aceh City in 2024 - Hayatunnufus Hayatunnufus; Farrah Fahdhienie; Fahmi Ichwansyah (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2026)
HIV/AIDS remains a significant global health challenge, particularly in maintaining the quality of life of affected individuals across physical, psychological, social, and environmental dimensions. In Banda Aceh City, the number of HIV/AIDS cases increased from 102 in 2022 to 149 in 2024, highlighting the need to address mental health aspects that are often overlooked. This study aimed to examine the factors associated with the quality of life of people living with HIV/AIDS, with mental health considered as a mediating variable. A quantitative cross-sectional study design was employed involving 115 respondents. Data were collected using structured questionnaires and analyzed using Smart PLS 3 for path analysis. The findings indicate that knowledge, treatment adherence, and stigma do not have a significant direct effect on quality of life. However, psychosocial factors influence quality of life indirectly through mental health. The structural model produced an R-square of 0.974, indicating that 97.4% of the variance in quality of life is explained by the proposed model. These results emphasize how crucial it is to improve mental health therapies and psychosocial support in order to enhance the quality of life for individuals living with HIV/AIDS. health services, communities, and healthcare providers are encouraged to work together in order to provide comprehensive and supportive care.